Non-Local Finite-Size Effects in the Dimer Model - Izmailian, N.Sh.; Priezzhev, V.B.; Ruelle, P. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We study the finite-size corrections of the dimer model on ∞ × N square lattice with two different boundary conditions: free and periodic. We find that the finite-size corrections depend in a crucial way on the parity of N, and show that, because of certain non-local features present in the model, a change of parity of N induces a change of boundary condition. Taking a careful account of this, these unusual finite-size behaviours can be fully explained in the framework of the c = -2 logarithmic conformal field theory.